Bosonic fortuity in vector models - Robert de Mello Koch; Animik Ghosh; Hendrik J. R. Van Zyl (Journal of High Energy Physics)
Abstract We investigate the space of U(N) gauge-invariant operators in coupled matrix-vector systems at finite N, extending previous work on single matrix models. By using the Molien-Weyl formula, we compute the partition function and identify the structure of primary and secondary invariants. In specific examples we verify, using the trace relations, that these invariants do indeed generate the complete space of gauge invariant operators. For vector models with f ≤ N species of vectors, the space is freely generated by primary invariants, while for f > N, secondary invariants appear, reflecting the presence of nontrivial trace relations. We derive analytic expressions for the number of secondary invariants and explore their growth. These results suggest a bosonic analogue of the fortuity mechanism. Our findings have implications for higher-spin holography and gauge-gravity duality, with applications to both vector and matrix models.